PERANAN PENGGUNAAN LAHANDI AREA TANGKAPAN SUNGAI SUNGEAN TERHADAP EUTROFIKASI DANAU TONDANO - Santi . Lumingkewas; Johan A. Rombang; Josephus I. Kalangi; Fabiola B. Saroinsong (Universitas Sam Ratulangi, 2013)
ABSTRACTEutrofication is one of the water pollution that caused by the increase ofthe consentrate of nutrient. This research studied conducted in catchment area ofSungean river sub DAS Noongan, Kab. Minahasa. The objective of this studywere to quantify the eutrofication’s rapid, in this case the value of Nitrogen andFosfor that caused by any land uses in catchment area of Sungean river sub DASNoongan.This research studied was done by taking the sample of water andquantifying water discharge in some point which had been chosen alongcatchment area of Sungean river that represent various land use. Then theconcentrate of N and P in water sample was analyzed in BARISTAND laboratory.Then the data of N and P That transported from each land uses, was analyzed instatistic with using Randomized Block Design (RBD) and spatial analisis(arcview).The result of research study showed that, each land uses gave effect tothe increase of lake eutrofication. Were in Tondano Lake from Sungean river forN was about 467,1076 mg/day and P was about 5,961849 mg/day. The biggestcontribution of N and P was from residential area, it was 464,2352 mg day-1 ha-1dan 5,961849 mg day-1 ha-1.Keywords : Eutrofikasi, Nutrient, River Of Sungean, Landuse